An Evaluation of the Resilience of Cities to Natural Hazards (Metropolis of Tabriz) - Parichehr Mesri Alamdari (تحقیقات کاربردی علوم جغرافیایی)
One major issue to be considered in today's cities is their resilience which plays an important role in reducing the damage and casualties caused by various natural hazards. These hazards often have devastating effects on human settlements, and resilient settlements in various managerial, physical, economic, and social aspects is a great way to enhance the effectiveness of cities in dealing with a variety of potential and unexpected crises. In this regard, addressing the resilience of cities in different aspects reveals the importance and necessity of research. The purpose of this study is to investigate the factors influencing the resilience of cities to natural disasters. The research method is applied in terms of purpose and descriptive-analytical in terms of methodology. The statistical population includes specialists and experts. FVIKOR model is used to analyze the components and characteristics, and EDAS method is used to show the condition of areas in terms of resilience. The results from Fuzzy VIKOR show the institutional component in the first place with the most score (zero) and the economic component in the last place with the score of 0.287. Also, the results from EDAS in different aspects of the studied areas show high resilience of districts 2 and 5 and low resilience of districts 4 and 8. Generally, more than 50% of Tabriz districts are less resilient.